2014
DOI: 10.1098/rsbl.2014.0659
|View full text |Cite
|
Sign up to set email alerts
|

Female social preference for males that have evolved via monogamy: evidence of a trade-off between pre- and post-copulatory sexually selected traits?

Abstract: When females mate with multiple males both pre- and post-copulatory sexual selections occur. It has been suggested that females benefit from polyandry when better-quality males are successful in sperm competition and sire high-quality offspring. Indeed, studies of experimental evolution have confirmed that sperm competition selects for both increased ejaculate quality and elevated offspring viability. Fewer investigations have explored whether these fitness benefits are evident beyond early life-history stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Modifications to traits that were not measured may have resulted in trade‐offs going undetected (e.g. see Firman, in mice and Simmons et al ., for a general review). However, as an ethical requirement our experimental animals were provisioned with unlimited access to food, water and shelter.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications to traits that were not measured may have resulted in trade‐offs going undetected (e.g. see Firman, in mice and Simmons et al ., for a general review). However, as an ethical requirement our experimental animals were provisioned with unlimited access to food, water and shelter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a reduction in testes interstitial tissue, and consequently a reduction in the density of Leydig cells, could result in a reduction in testosterone production and influence the quality or frequency of scent‐marks produced by males. A recent study has revealed that sexually receptive females spent more time associating with males from the monogamous populations compared to males from the polygamous populations, suggesting that these males have a precopulatory advantage that could be attributable to an intrinsic quality associated with the scents that they produce (Firman ). The divergence in testes tissue composition among males evolving with and without sperm competition reported here certainly warrants further research into evolutionary trade‐offs between pre‐ and postcopulatory sexually selected traits.…”
Section: Discussionmentioning
confidence: 99%
“…) can be estimated in experimental‐evolution studieses (e.g., Simmons and Garcia‐Gonzalez ; Crudgington et al. ; Firman and Simmons ; Firman ; Perry et al. ).…”
mentioning
confidence: 99%
“…Artificial selection allows to shed light on previously hidden covariances, either positive or negative, among sexually selected traits, or to highlight the limits imposed by selection on other fitness components (e.g., Wilkinson and Reillo 1994;Von Schantz et al 1995;Pitnick and Miller 2000;Ahuja and Singh 2008;Wigby et al 2009;Booksmythe et al 2016). Alternatively, the evolutionary response of sexual traits to specific conditions imposed by the experimenter (Kawecki et al 2012) can be estimated in experimental-evolution studieses (e.g., Simmons and Garcia-Gonzalez 2008;Crudgington et al 2009;Firman and Simmons 2011;Firman 2014;Perry et al 2016).…”
mentioning
confidence: 99%